The evaluation of learning by competencies in the Medicine Degree: the proposal of a new model for UNAN- Managua - Molina Saavedra, Karla E.; Prieto Jiménez, Esther; Dominguez Fernandez, Guillermo (IJERI: International Journal of Educational Research and Innovation, 2022)
This papper presented gathers the main results obtained after the completion of a doctoral thesis by the first signing author. Under the title "Assessment model of learning by competencies: Clinical area of ​​the Medicine degree, UNAN- Managua", its purpose was to design an evaluation model of learning by competencies for the Medicine degree career. To achieve this objective, a mixed study was carried out, using a multiple sequential intermethod triangulation (quali-quanti-quali) and intra-qualitative method of the information collected. The main conclusions led to the identification that the current teaching evaluation practices are basically behaviorist, the scarcity in the different competences that are evaluated at the discretion of the teacher of the different care teaching units and with a limited variety of evaluation techniques and instruments was evidenced. The research process ended with an evaluation proposal, based on the CEFIMM model (Context, Evaluator/Evaluated, Purpose, Moments, Methodology) in which the evaluation is viewed holistically and includes the evaluation of the deferred phase.